Development of Analysis of Loss Sources of Vehicles - Pálinkás , Sándor; Juhász, György; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2020)
Vehicle fuel consumption can be significantly influenced by various types of losses such as loss from bearing, aerodynamic drag and rolling drag. It is important to highlight that fuel consumption reduction can be only achieved when those losses are reduced that are induced during the operation.The aim of our work group is to define the calculation method and the magnitude of the losses of the vehicles. These parameters are intended to be serve as input parameters for future energetic modelling of vehicles.